Mobilizing adolescents and young women to promote healthy diets in urban settings of Colombia and Vietnam: Lessons from two action-research programs - Bergeron, Gilles; Nguyen, Phuong Hong; Correa Guzman, Nathalia; Tran, Lan Mai; Hoang, Nga Thu; Restrepo Mesa, Sandra (Wiley, 2023)
Adolescent and young women face grave nutrition challenges, but limited evidence exists on solutions to improve their diets. Action-research was done over 3 years (2020–2022) in secondary cities of Colombia (Medellin) and Vietnam (Thai Nguyen) to identify nutrient deficits in adolescent and young women diets; elaborate food-based recommendations to improve their nutritional status using Optifood linear programming; and engage respondents in incorporating suggested recommendations to their diet using a Social Innovation Challenge approach. A total of 1001 respondents were interviewed in Vietnam, 793 in Colombia. The probability of nutrient inadequacy in both locations was highest for iron and calcium, followed by the risk of deficiency for several other vitamins and minerals. Social Innovation Challenge teams (11 in Vietnam, 9 in Colombia) were created and supported in developing solutions to improve diets and tackle those deficiencies. Awards and resources were transferred to the most promising solutions to enable their implementation. Pre/post measurements of the interventions’ impact using the Global Diet Quality Score as outcome metric showed significant improvement in the diets of Challenge participants. After introducing a series of companion articles that offer detailed results on those various steps, this paper draws strategic lessons from an action-research perspective.